Sustaining soil productivity in intensive African agriculture - Ahenkorah, Y.; Dowuona, G.N.N.; Owusu-Bennoah, E. (Technical Centre for Agricultural and Rural Cooperation, 1995)
The papers are grouped into four categories: land management practices for intensive agriculture; overcoming soil constraints; technology adoption; and planned research and development.